Szacowanie nadziemnej biomasy drzewnej lasów w Polsce na potrzeby sprawozdawczości EKG/FAO i UNFCCC - Jabłoński, Marek; Budniak, Piotr (Leśne Prace Badawcze, 2014)
The United Nations Framework Convention on Climate Change and the Kyoto Protocol have committed member states to reduce greenhouse gas emissions by, among others, promoting the increase of carbon sequestration by carbon sinks (including woody biomass in forests). In order to achieve these objectives, an international reporting system was designed. The stock of woody biomass depends on several environmental and managerial factors, which determine species composition and age structure of a forest as well as characteristics of individual trees. Estimating above ground woody biomass, especially on a nation-wide level, is generally based on the application of conversion factors to known characteristics such as the volume of the growing stock. The application of default conversion factors, as proposed by international guidelines, however, is questionable, since inventory systems for and definitions of growing stock differ from country to country. In this paper, the methods used in Poland to estimate woody biomass for the FAO and the UNFCC reporting, were presented and analysed. We also analysed the influence of some stand and tree characteristics, such as tree species composition and content of bark and its density, on the stock of woody biomass. We conclude that issues not addressed in the IPCC guidelines, such as big differences in wood and bark density, especially for pine, need to be taken into consideration when making estimations. Moreover, the results of this paper show that biomass conversion and expansion factors (BCEF) proposed by IPCC are not adequate for Polish conditions.